EDUCATION MANAGEMENT PERSPECTIVES PROPHET IBRAHIM - sulistiawati tia _; Danial Hilmi (UIR Press, 2019)
It is important to emulate the education management perspectives prophet Ibrahim, where management of education has existed since the time of the prophets and the nature of management has existed and has grown naturally since the existence of this life. We first learned management from the time of the Prophet Adam to the time of the Prophet Muhammad. Here researchers focus more on the education management perspectives prophet Ibrahim. As mentioned in the Qur’an, it is emphatic that God established the Prophet Ibrahim with the nickname as